Strategi Pengurus NU Medan Dalam Pengelolaan Madrasah Tsanawiyah NU Medan (Studi Implementasi Peraturan Menteri Agama) - Nia Nurinaya; Kamil Kamil (Yayasan Rahmat Islamiyah, 2025)
The purpose of this study is to gain an understanding of the strategies employed by MTs NU Medan in managing Madrasah Tsanawiyah Nahdlatul Ulama Medan in implementing the regulations issued by the Ministry of Religious Affairs. This research is qualitative in nature, utilizing observation, in-depth interviews, and document analysis as methods of data collection. The results of this study are expected to assist educational institutions in managing madrasahs in accordance with the implementation of the Ministry of Religious Affairs regulations.